Exploring Students’ Perceptions of An Intensive English Course Program for Speaking Development - Haritsah Ni’matul Khoiriyah; Luluk Choirun Nisak Nur, M.Pd. (Retain: Journal of Research in English Language Teaching, 2026)
This research investigates students’ perceptions toward the Intensive English Course program in developing speaking skills among EFL students at MA Unggulan Wahab Hasbulloh. Employing an explanatory sequential mixed-method design, quantitative data were collected through a questionnaire distributed to students participating in the program, followed by qualitative interviews to obtain deeper insights into their experiences and opinions. The findings indicate that the Intensive English Course contributes positively to students’ speaking development, particularly in building confidence, improving fluency, and expanding oral vocabulary through continuous speaking exposure and communicative activities. Most students reported that the program provided a supportive environment that encouraged active participation and reduced speaking anxiety. The qualitative findings also indicated that various speaking activities, such as free conversation and language shows, effectively supported students’ speaking performance. Overall, the Intensive English Course was perceived as beneficial and effective in improving speaking skills and creating a communicative speaking atmosphere for EFL learners in this context. Keywords: Students’ perception; Intensive English Course; Speaking Skills; EFL Learners